THE PLACE OF ROLE PLAY ACTIVITIES IN TEACHING ENGLISH LITERATURE - Ibragimova Dilafruz Shukhratovna; Muradova Mushtariy (Ta'lim innovatsiyasi va integratsiyasi, 2024)
The article examines the positive role of role-play activities in language teaching, the influence of applying the method of role-play activities on students' learning process of foreign language. Through a comprehensive review of the literature and an imaginative data collection process, the study highlights the benefits of incorporating role-play activities in language classrooms. The results emphasize the importance of integrating role-play activities into language teaching to promote interactive and meaningful language use, ultimately facilitating students' language learning experiences and outcomes.